2009
DOI: 10.1097/hjh.0b013e32831ffec7
|View full text |Cite
|
Sign up to set email alerts
|

Renal functional, not morphological, abnormalities account for salt sensitivity in Dahl rats

Abstract: We conclude that renal functional, not morphological, abnormalities cause salt sensitivity in Dahl rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Aldosterone, acting through the mineralocorticoid receptor, is a major regulator of ENaC. While studies in the early 1990s showed lower levels for plasma aldosterone in S vs. R (Cover et al 1995), recent studies show similar or higher levels in S rats (Manger et al 2009;Takeda et al 2007). Plasma aldosterone concentration decreased with high salt in both strains, consistent with previous studies (Aoi et al 2007;Farjah et al 2003;Zhu et al 2009), but remained somewhat higher in S. This suggests a similar regulation of plasma aldosterone by high salt.…”
Section: Regulators Of Renal Enacsupporting
confidence: 81%
“…Aldosterone, acting through the mineralocorticoid receptor, is a major regulator of ENaC. While studies in the early 1990s showed lower levels for plasma aldosterone in S vs. R (Cover et al 1995), recent studies show similar or higher levels in S rats (Manger et al 2009;Takeda et al 2007). Plasma aldosterone concentration decreased with high salt in both strains, consistent with previous studies (Aoi et al 2007;Farjah et al 2003;Zhu et al 2009), but remained somewhat higher in S. This suggests a similar regulation of plasma aldosterone by high salt.…”
Section: Regulators Of Renal Enacsupporting
confidence: 81%
“…This system may be blunted by RSV treatment [22], [31] thus reducing the cardiac hypertrophy. In contrast, in DSS rats, circulating RAS is rather inhibited [32] and hypertension is mostly linked to blood volume expansion [33] so that potential anti-RAS activity of RSV does not reduce hypertension. This suggests that resveratrol may have separate, beneficial effects on hypertension and cardiac hypertrophy, and thus the benefits of resveratrol may depend on the etiology of HF.…”
Section: Discussionmentioning
confidence: 89%
“…Fourth, this model is especially good for studying renal disease. Functional abnormalities in the kidneys account for salt sensitivity and hypertension, not hypertension‐induced renal damage . Furthermore, Dahl‐S rats develop a progressive decline in glomerular filtration rate as a consequence of hypertension .…”
Section: Discussionmentioning
confidence: 99%